SERUM C3 AND SERUM C4 COMPLEMENT IN PATIENTS WITH BURN TRAUMA AND CORRELATION WITH BURN INJURY SEVERITY - Arslanagic, Selma; Karamehic, Jasenko (Sanamed, 2022)
Introduction: Burns, depending on the degree of severity, induce a significant pathophysiological response in the body. The complement system participates in the body’s defenses as well as in immune responses after burn-induced trauma. Objectives: The main objective of the study was to examine how burn severity affects serum C3 and serum C4 complement values; whether burn severity correlates with serum C3 and C4 complement, and establish the predictive value of the serum C3 complement and serum C4 complement for assessing the severity of the burn. Patients and methods: According to the degree of TBSA, patients were classified into three groups: group with %TBSA<15% (30 patients), group with %TBSA >15% -25% (30 patients), and group with %TBSA > 25% to 40% (30 patients). According to the depth of burns, patients were classified into two groups partial-thickness burns (39 patients) and full-thickness burns (51 patients). We followed laboratory parameters: value serum C3 complement and serum C4 complement on the first and seventh day after burn trauma. Results: Serum C3 complement was significantly lower in patients with %TBSA>25%-40% and in the group with %TBSA>15%-25% compared to patients with %TBSA<15% on the first and seventh day after burn trauma. Serum C3 complement was significantly lower in patients with %TBSA >15%-25% compared to patients with %TBSA<15% on day one and day seven after burn trauma. Serum complement C4 was not significantly different between burn groups on the first and seventh day. Full-thickness burns have significantly lower levels of serum complement C3, compared to partial-thickness burns, on the 1st and 7th day. Full-thickness burns result in a decrease in serum C4 complement compared to partial-thickness burns on the 7th day after burn trauma, but this decrease is not significant. On the 1st day after burn trauma, we found a negative correlation between %TBSA with serum C3 complement. Serum C4 complement was not correlated with %TBSA on the day 1st. Conclusions: %TBSA and depth of burn result in a significant decrease in serum C3 complement but not serum C4 complement. There is a negative correlation of %TBSA and C3 complement but not serum C4 complement on the 1st day after burn trauma. Serum C3 complement is a significant predictor of burn severity. The predictory significance of the C4 complement is not statistically significant.